Advances in Robotics, Automation and Data Analytics Selected Papers from iCITES 2020 - Mat Jizat, Jessnor Arif; Khairuddin, Ismail Mohd; Mohd Razman, Mohd Azraai; Ab. Nasir, Ahmad Fakhri; Abdul Karim, Mohamad Shaiful; Jaafar, Abdul Aziz; Hong, Lim Wei; Abdul Majeed, Anwar P. P.; Liu, Pengcheng; Myung, Hyun; Choi, Han-Lim; Susto, Gian-Antonio (Advances in Intelligent Systems and Computing, 2021)
XV, 415 p. 229 illus., 184 illus. in color.